Techno-economic analysis of a megawatt-scale thermoplastic resin wind turbine blade. (February 2019) - Murray, Robynne E.; Jenne, Scott; Snowberg, David; Berry, Derek; Cousins, Dylan
Abstract: Two-part, in-situ reactive thermoplastic resin systems for composite wind turbine blades have the potential to lower the blade cost by decreasing cycle times, capital costs of both tooling and equipment, and energy consumption during manufacturing, and enabling recycling at the end of the blade life. This paper describes a techno-economic model used to estimate the cost of a thermoplastic wind turbine blade relative to a baseline thermoset epoxy blade. It was shown that a 61.5-m thermoplastic blade costs 4.7% less than an equivalent epoxy blade. Even though the thermoplastic resin is currently more expensive than epoxy, this cost reduction is primarily driven by the decreased capital costs, faster cycle times, and reduced energy requirements and labor costs. Although thermoplastic technology for resin infusion of wind turbine blades is relatively new, these results suggest that it is economically and technically feasible and warrants further research. Highlights: A thermoplastic wind turbine blade could reduce the manufactured blade cost by 4.7% compared to a thermoset epoxy blade. An assumed 50% reduction in blade tooling cost for the thermoplastic blade had a significant effect on the cost. The thermoplastic resin cost would have to increase by over 25% for the thermoplastic blade to be the same price as the epoxy blade.